Pemberdayaan Dan Pendidikan Warga Ex Lokalisasi di Kota Lubuklinggau - Helandri, Joni; Sari, Juliah Indah; Hasani, Muhammad; Saputra, Muhammad Leo; Indika, Puspa; Munawaroh, Serli (Edification Journal : Pendidikan Agama Islam, 2022)
This research aims to review the efforts to empower ex-localization communities with certain approaches. In this study using descriptive qualitative research, the data sources are in the form of interviews, documentation, the data obtained from the research is analyzed and produced. One of the efforts made so that ex-localization residents can live independently is carried out by coaching through religious approaches such as deepening religious knowledge, education, and an approach to economic empowerment by training and making ex-localization residents ready to work to be able to compete in accordance with the demands of the community